SISTEM ALARM MOBIL MENGGUNAKAN MIKROKONTROLER AT89S52 BERBASIS SMS - Balza Achmad; Wahyu Sapto Aji; Wahyu Paningal (Universitas Ahmad Dahlan, 2008)
This study aims to design a car alarm system. The system is designed to be able to sound an alarm (sound) alarm and send an SMS message to a phone alarm car owners. The composition of the car alarm system hardware using AT89S52 microcontroller based SMS in this study, consists of 4 main parts of the circuit, which is a series of minimum system microcontroller, power supply, serial communication, Input / Output. In the text of SMS sent and received from mobile (cell phone) to the SMS center or SMS Center to flow in the form of PDU (Protocol Data Unit). In the SMS format is divided into a number of segments each segment of data that it has a specific purpose. The segments are: sms center number, destination number, the bytes for the purposes of this sms settings and the most important is the content of the text messages that have been modified in the form of a PDU. To be able to send or upload the data sms to mobile phones and ordered it to submit data necessary instructions sms AT Command. The results showed that the performance of the alarm system that is designed to work with either.